Primary wound closure in acute appendicitis of children Comparison between continuous (intradermal) and Interrupted Suturing - ناصر محمد; كنعان سمير; مرعي كلان (Latakia University Journal -Medical Sciences Series, 2021)
Background and Aim of study : finding an optimal way to close the wound after acute appendectomy in children. Methods : the research sample included 79 children diagnosed with acute appendicitis and the subjected to an appendectomy during the year 2019 -2020 and comparison was made between two groups of children ,the first was suturing the wound by the simple interrupted and the second by the continuous intradermal suture technique, the wound was evaluated after 1week , two weeks then after a month postoperative. Results: infection occurred in 7.7% of all patients , the percentage of wound infection by the interrupted simple suture method was 5,1% and within the continuous intradermal suture method 2,1%whithout any cases of dehiscence. Conclusion : primary closure of the wound in cute appendicitis by continuous intradermal suturing is a safe technique even in the case of perforating, gangrenous or abscess.